Evolution of the Development of the Science of Interpretation from the Time of the Prophet SAW to the Pentadwinan Period - Jahira Salsabila Nurul Imam; Tami Dewi Puspa Rahayu; Wanda Jawhariyah Sya’baniyah; Dede Kurniawan (Tilawah: Journal of Al-Qur'an Studies, 2025)
This study examines the evolution of the development of Qur'anic exegesis from the time of the Prophet Muhammad (peace be upon him) to the period of codification. During the Prophet’s lifetime, exegesis was characterized by its authenticity, as it was directly sourced from divine revelation and his explanations to the companions. After the Prophet’s death, the companions continued the process of interpretation based on their understanding of the context of the verses, transmitted reports (riwayat), and independent reasoning (ijtihad) grounded in Shari'ah principles. Subsequently, the generation of the tabi'in and later scholars enriched the methodology of tafsir through linguistic, historical, and analytical approaches, alongside the development of supporting sciences such as Arabic linguistics and the study of asbab al-nuzul (occasions of revelation). The period of codification marked a significant milestone in the intellectual history of Islam, characterized by systematic efforts to collect, compile, and document the interpretations of the companions and tabi'in. This research employs a historical-descriptive method to trace the changes, methodological developments, and socio-historical dynamics that influenced Qur'anic exegesis throughout the early Islamic period. The findings reveal that the evolution of tafsir was driven by the community’s need for deeper understanding of the Qur'an, the complexity of socio-political contexts, and the advancement of Islamic sciences. It illustrates that the evolution of Qur'anic exegesis was not merely a response to practical needs but also a continuous scholarly process within Islamic civilization.